2003
DOI: 10.1046/j.1365-313x.2003.01854.x
|View full text |Cite
|
Sign up to set email alerts
|

The YORE‐YORE gene regulates multiple aspects of epidermal cell differentiation in Arabidopsis

Abstract: SummaryWe have identi®ed a new Arabidopsis mutant, yore-yore (yre), which has small trichomes and glossy stems. Adhesion between epidermal cells was observed in the organs of the yre shoot. The cloned YRE had high homology to plant genes involved in epicuticular wax synthesis, such as ECERIFERUM1 (CER1) and maize GLOSSY1. The phenotype of transgenic plants harboring double-stranded RNA interference (dsRNAi ) YRE was quite similar to that of the yre mutant. The amount of epicuticular wax extracted from leaves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 35 publications
(59 reference statements)
11
114
0
Order By: Relevance
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionsupporting
confidence: 54%
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionsupporting
confidence: 54%
“…Scanning electron microscopy samples were prepared and observed as described previously (Kurata et al, 2003).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…DEX1 is a novel protein of unknown function thought to be localized to the plasmalemma. Other genes associated with exine production and male fertility include YORE-YORE/WAX2/FACELESSPOL-LEN1, encoding an enzyme apparently involved in wax biosynthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) and the rice (Oryza sativa) Wax-deficient anther1 gene, a homolog of the Arabidopsis ECERIFERUM1 gene that encodes a putative membrane protein apparently required for very-longchain fatty acid metabolism (Jung et al, 2006).…”
Section: Introductionmentioning
confidence: 99%